The Deconstruction of the Cartesian Dichotomy of Black and Whitein William Blake’s The Little Black Boy - Gunes, Ali (Journal of History Culture and Art Research, 2015)
The Deconstruction of the Cartesian Dichotomy of Black and Whitein William Blake’s The Little Black Boy Abstract This paper discusses English Romantic Poet William Blake’s anti-racial views in his poem The Little Black Boy. In so doing, it focuses upon how Blake attempts to deconstruct the Cartesian dichotomy of Western world view, a dichotomy which has usually been based on “the theory that the universe has been ruled from its origins by two conflicting powers, one good and one evil, both existing as equally ultimate first causes.” In this binary and hierarchal relationship, there are two essential terms in which one term is absolutely regarded as primary or fundamental in its essence, whereas the other term is considered secondary or something that lacks originality and presence. Once this equation is applied to the relationship between black and white people, it will easily be seen in the Western world that white people are always primary or fundamental to black-skinned people, and thus the perception behind this binary and hierarchal relationship seems the root of all the racial problems between black and white. This paper argues that Blake strives to deconstruct radically in The Little Black Boy the basis of this binary and hierarchal relationship which has been carried out for centuries in the Western world to segregate and then control the lives of black people. Finally, the paper maintains that Blake also shows a strong aspiration for creating an egalitarian society free of discrimination and injustices at a time when anti-slavery campaigns hit the top on both sides of Atlantic.